Identifikasi Kerusakan Pada Mesin Consumer Pack Menggunakan Metode FMEA Di PT. Bungasari Flour Mills - Abidillah, Abidillah; Rahmatullah, Asep; Muhammad, Irfan (Jurnal Teknik Juara Aktif Global Optimis, 2022)
Based on the product demand data of PT. Bungasari Flour Mills saw an increase in wheat flour production capacity of 600,000 MT in 2021. Conditions that often occur are damage to production machines, including consumer packs, carton erector machines, robot packer machines and carton sealer machines. Machines that often experience damage are consumer pack machines with 75 times of damage with a downtime of 487 hours. This study aims to determine the cause of failure of the consumer pack machine and can provide suggestions for optimal maintenance improvements. The method or approach in this study uses the Failure Mode And Analysis (FMEA) method which is used to identify the cause of machine failure based on the Risk Priority Number (RPN) value to determine the highest level of risk. The results of the study using the Failure Mode And Analysis (FMEA) method based on the value of the Risk Priority Number (RPN) obtained the RPN value of 872. This is because of the high downtime, it can be seen that the vertical sealer and horizontal sealer components have the highest RPN value of 216